Colonial writing and the New World, 1583-1671 : allegories of desire - Scanlan, Thomas (Cambridge University Press, 1999)
Colonial Writing and the New World, 1583-1671 offers an account of the simultaneous emergence of colonialism and nationalism during the early modern period. It suggests that colonialism is best understood as a phenomenon which had profound significance for people on both sides of the Atlantic.
Keywords: American prose literature -- Colonial period, ca. 1600-1775 -- History and criticism.; English prose literature -- Early modern, 1500-1700 -- History and criticism.; United States -- History -- Colonial period, ca. 1600-1775 -- Historiography.; Great Britain -- Colonies -- America -- History -- 16th century.; Great Britain -- Colonies -- America -- History -- 17th century.; Indians of North America -- First contact with other peoples.; Great Britain -- Colonies -- America -- Historiography.; Colonies in literature.; America -- In literature.; Desire in literature.; Allegory.; Prose américaine -- ca 1600-1775 (Période coloniale) -- Histoire et critique.; Prose anglaise -- 17e siècle -- Histoire et critique.; Peuples autochtones -- Premiers contacts avec d'autres peuples -- Amérique du Nord.; Colonies dans la littérature.; Désir dans la littérature.; Allégorie.; Amérique dans la littérature.; Prose anglaise -- 16e siècle -- Histoire et critique.; États-Unis -- Histoire -- ca 1600-1775 (Période coloniale) -- Historiographie.; Grande-Bretagne -- Colonies -- Amérique -- Historiographie.; Grande-Bretagne -- Colonies -- Amérique -- Histoire -- 16e siècle.; Grande-Bretagne -- Colonies -- Amérique -- Histoire -- 17e siècle.; Amérique -- Dans la littérature.; allegories (literary genre); LITERARY CRITICISM -- American -- General.; Allegory; American prose literature -- Colonial period; British colonies; Colonies in literature; Desire in literature; English prose literature -- Early modern; Historiography; Indians of North America -- First contact with other peoples; Literature; America; United States; 1500-1775; Electronic books.; History; Criticism, interpretation, etc.